Determinant Factors Affecting Self-Medication Behavior In Breastfeeding Mothers - Murwati Murwati; Suroso Suroso; Nur Atikah (Interest : Jurnal Ilmu Kesehatan, 2022)
Background: Self-medication practices can be a source of medication errors, especially for nursing mothers, because almost all drugs taken by nursing mothers are detected in breast milk, even though the concentrations are low. It can be prevented by identifying the determinants of self-medication. Methods: This study is a cross-sectional quantitative analytic study. A sample of 150 mothers was choosen by purposive sampling with the criteria for breastfeeding a baby with a maximum age of 6 months. The instrument used is a questionnaire on the determinants of self-medication behavior in breastfeeding mothers. The questionnaire has been tested for validity with Pearson's test (p < 0.05) and reliability with Chronbach's alpha (0.78). Data analysis with chi-square and multivariate tests Results: The statistical analysis showed a significant association between education level, medical history, drug price, and information media and self-medication behavior in breastfeeding mothers. However, those that had an impact were the history of the disease (p = 0.014), education level (p = 0.024), and drug price (p = 0.006). Conclusion: The determinants of self-medication behavior in breastfeeding mothers were disease history, drug prices, and education. Further research is needed regarding the rationality of self-medication to determine the optimization and safety of drugs used by breastfeeding mothers.